2019
DOI: 10.1002/bab.1827
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular crowding effects on transcription and translation are regulated by free magnesium ion

Abstract: Cell‐free metabolic engineering is an emerging and promising alternative platform for the production of fuels and chemicals. In recent years, macromolecular crowding effect, which is an important function in living cells but ignored in cell‐free systems, has been transferred to cell‐free protein synthesis (CFPS). However, inhibitory effects of crowding agents on CFPS were frequently observed, and the mechanism is unclear. In this study, free Mg2+ was found to be a key factor that can regulate the macromolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Magnesium ion is one of the key factors affecting protein synthesis (Figure 5a). It was found that Mg 2+ as a cofactor was involved in the transcription and translation processes 45 . So first of all, the selected four combinations (dimer I + H, trimer K + I and L + H, and multimer K + L) (Figure 5b) were coexpressed in the cell‐free system containing 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 100, or 200 mM Mg ion concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Magnesium ion is one of the key factors affecting protein synthesis (Figure 5a). It was found that Mg 2+ as a cofactor was involved in the transcription and translation processes 45 . So first of all, the selected four combinations (dimer I + H, trimer K + I and L + H, and multimer K + L) (Figure 5b) were coexpressed in the cell‐free system containing 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 100, or 200 mM Mg ion concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Such conditions are expected to alter many properties of ctRSD circuits. For example, ion availability and molecular crowding influence transcription, RNA folding and ribozyme catalysis, and strand displacement. ,, Further, encapsulation and localization of RNA can influence RNA folding and ribozyme catalysis, , and strand displacement reactions . Strand displacement reactions are also influenced by the presence of non-target nucleic acids, and the presence of RNases will introduce sequence and structure specific degradation rates .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the enhancing effects of BSA as a crowding agent, which reduces the inhibitory effect on the reaction, stabilizes the enzymes, and prevents nucleic acids from binding to the reaction containers. [ 29 ] Perhaps the enhancer effect of BSA along with the specific effects of proteinase K removes the inhibitory effect of interferer proteins and helps improve the efficacy of the LAMP reactions that do not occur with BSA or Triton X-100 alone (methods 4 and 6). However, the combination of BSA and proteinase K with Triton X-100 detergent may help better RNA release, which in turn gives us the possibility of increasing dilution factor.…”
Section: Discussionmentioning
confidence: 99%